The physiological and emotional effects of touch: Assessing a hand-massage intervention with high self-critics. (April 2017) - Maratos, Frances A.; Duarte, Joana; Barnes, Christopher; McEwan, Kirsten; Sheffield, David; Gilbert, Paul
Abstract: Research demonstrates that highly self-critical individuals can respond negatively to the initial introduction of a range of therapeutic interventions. Yet touch as a form of therapeutic intervention in self-critical individuals has received limited prior investigation, despite documentation of its beneficial effects for well-being. Using the Forms of Self-Criticism/Self-Reassuring Scale, 15 high- and 14 low- self-critical individuals (from a sample of 139 females) were recruited to assess how self-criticism impacts upon a single instance of focused touch. All participants took part in a hand massage- and haptic control- intervention. Salivary cortisol and alpha amylase, as well as questionnaire measures of emotional responding were taken before and after the interventions. Following hand massage, analyses revealed cortisol decreased significantly across all participants; and that significant changes in emotional responding reflected well-being improvements across all participants. Supplementary analyses further revealed decreased alpha amylase responding to hand massage as compared to a compassion-focused intervention in the same (highly self-critical) individuals. Taken together, the physiological and emotional data indicate high self-critical individuals responded in a comparable manner to low self-critical individuals to a single instance of hand massage. This highlights that focused touch may be beneficial when first engaging highly self-critical individuals with specific interventions. Highlights: Self-critical individuals can respond negatively to therapeutic interventions. Touch as an initial therapeutic intervention has received limited investigation. Hand-massage led to cortisol reductions in both low and high self-critics. Hand-massage led to positive emotional responding in both low and high self-critics. Touch/massage may offer new avenues for initial therapeutic interventions.